Transfer of metformin across the rat placenta is mediated by organic cation transporter 3 (OCT3/SLC22A3) and multidrug and toxin extrusion 1 (MATE1/SLC47A1) protein - Ahmadimoghaddam, Davoud; Staud, Frantisek (Reproductive toxicology (Elmsford, N.Y.), 2013)
In our previous studies we described functional expression of organic cation transporter 3 (OCT3) and multidrug and toxin extrusion 1 (MATE1) protein in the rat placenta. Since metformin is a substrate of both OCT3 and MATE1, in this study we used the model of dually perfused rat placenta to investigate the role of these transporters in metformin passage across the placenta. We observed concentration-dependent transplacental clearance of metformin in both maternal-to-fetal and fetal-to-maternal directions; in addition metformin crossed the placenta from the fetal to maternal compartment even against its concentration gradient. This transport was completely inhibited by MPP(+), a common OCT3 and MATE1 inhibitor. Furthermore, we observed that the oppositely directed H(+)-gradient can drive the secretion of metformin from placenta to maternal circulation, confirming apical efflux of metformin from trophoblast by MATE1. In conclusion, we suggest an important role of OCT3 and MATE1 in the transplacental transfer of metformin.
Keywords: Rats, Wistar; Organic Cation Transport Proteins; proteiny přenášející organické kationty; přenašeče organických aniontů nezávislé na sodíku; Pregnancy; těhotenství; techniky in vitro; Antiporters; Placenta; potkani Wistar; antiportéry; krysa rodu Rattus; Maternal-Fetal Exchange; maternofetální výměna látek; placenta; metformin; hypoglykemika; Animals; ženské pohlaví; zvířata; Rats; Metformin; Organic Anion Transporters, Sodium-Independent; Hypoglycemic Agents; Female; In Vitro Techniques